2012
DOI: 10.1186/1556-276x-7-457
|View full text |Cite
|
Sign up to set email alerts
|

Photonic bandgap of inverse opals prepared from core-shell spheres

Abstract: In this study, we synthesized monodispersed polystyrene (PS)-silica core-shell spheres with various shell thicknesses for the fabrication of photonic crystals. The shell thickness of the spheres was controlled by various additions of tetraethyl orthosilicate during the shell growth process. The shrinkage ratio of the inverse opal photonic crystals prepared from the core-shell spheres was significantly reduced from 14.7% to within 3%. We suspected that the improvement resulted from the confinement of silica she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This method requires a known value for 𝑛 eff , and assumes a perfectly filled IO structure with 𝜑 IO = 0.26. Some reports [53][54][55][56] have suggested that inverse opals feature a less than an optimal filling fraction. A variation to the filling fraction 𝜑 IO of an IO would prevent an accurate determination of 𝑛 eff via Eqs.…”
Section: Solvent Filling Of Inverse Opals and The Nature Of Structura...mentioning
confidence: 99%
See 1 more Smart Citation
“…This method requires a known value for 𝑛 eff , and assumes a perfectly filled IO structure with 𝜑 IO = 0.26. Some reports [53][54][55][56] have suggested that inverse opals feature a less than an optimal filling fraction. A variation to the filling fraction 𝜑 IO of an IO would prevent an accurate determination of 𝑛 eff via Eqs.…”
Section: Solvent Filling Of Inverse Opals and The Nature Of Structura...mentioning
confidence: 99%
“…In other cases [50,51], such as those with inverse opals prepared via annealing an opal template, there is a clear difference between the estimation of material properties from the spectral data and the independently measured microscopy data. It has been suggested that the optical behavior of inverse opal materials is inherently different from the reciprocal of an opal, with the possibility of an axial compression [51], reduced unit cell parameter [52] and, most commonly, reduced crystalline material volume fractions [53][54][55][56][57] suggested as possible explanations. Currently, there is an absence of consensus on the explanation underpinning the differences observed in the PBG for inverse opal structures.…”
Section: Introductionmentioning
confidence: 99%
“…First is the vertical self-assembly of PS spheres onto the clean ITO substrate as sacrificial templates. The photonic bandgap of io-CBO can be adjusted by varying the size of PS spheres (200 and 400 nm) . Second is the infiltration of CBO precursors into the voids of PS templates.…”
Section: Resultsmentioning
confidence: 99%
“…The photonic bandgap of io-CBO can be adjusted by varying the size of PS spheres (200 and 400 nm). 26 Second is the infiltration of CBO precursors into the voids of PS templates. Third is the removal of PS spheres by calcination in the air to obtain CBO inverse opals.…”
Section: Optical Simulationsmentioning
confidence: 99%